Peran Intellectual Capital Serta Intensitas Biaya Penelitian dan Pengembangan: Suatu Analisis Kinerja Keuangan Perusahaan - Fauzi Nurul Iman Gunawan; Dewi Susilowati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
This research aims to examine the effect of intellectual capital and the intensity cost of research and development on the company's financial performance. Based on the study of literature in the literature review formed research questions, namely 1). How Influence of Intellectual Capital on Company Performance 2). How the influence of intensity cost of research and development on the company's financial performance. The type of data used is secondary data. Data collection method is literature study. The method to be used for this study is the study of literature. The data obtained are compiled, analyzed, and concluded so as to obtain conclusions regarding the study of literature. The results showed that there was a relationship regarding intellectual capital and the intensity of research and development costs to the company's financial performance.Keywords: Intellectual Capital, Research and Development Costs, and Financial Performance.